NUCLEON MOMENTUM DISTRIBUTIONS AND ELASTIC ELECTRON SCATTERING DIFFERENTIAL CROSS SECTIONS FOR SOME 2s-1d SHELL NUCLEI - Hamoudi, A K (Al-Nahrain Journal of Science, 2010)
The nucleon momentum distributions for the ground state and elastic electron scatteringdifferential cross sections have been calculated in the framework of the coherent fluctuation modeland expressed in terms of the weight function (fluctuation function). The weight function has beenrelated to the nucleon density distributions of nuclei and determined from theory and experiment.The feature of long-tail behavior at high momentum region of the nucleon momentum distributionshas been obtained using both theoretical and experimental weight functions. An A-dependence ofthe nucleon momentum distributions has been clearly found in the region of high momentumcomponent k 3 fm1. The observed differential cross sections for electron scattering from20Ne, 24Mg, 28Si and 32S nuclei are very well reproduced by the present calculations throughoutall values of scattering angle q.